CYTOTOXICITY OF Phaleria macrocarpa (Scheff.) Boerl. FRUIT MEAT AND SEED ETHANOL EXTRACT TO MONONUCLEAR PERIFER NORMAL CELL OF HUMAN BODY - Endang Astuti; Deni Pranowo; Santi Dwi Puspitasari (Universitas Gadjah Mada, 2006)
There were many research on Phaleria macrocarpa (Scheff.) Boerl. fruit for its activity as possible anticancer. However, there wasn't investigation that P. macrocarpa seed and fruit meat ethanol extract effect to normal cell. The research was conducted to identify the ethanol extract of P. macrocarpa for cytotoxic activity against mononuclear perifer normal cell of human blood. The research comprised several sections including P. macrocarpa seed and fruit meat maceration with ethanol, and the cytotoxic activity test against mononuclear normal cell. The results showed that the ethanol extract of P. macrocarpa fruit meat and seed was slightly toxic against mononuclear normal cell with the LC50 of 3817.54 μg/mL and 1349.29 μg/mL respectively. Tamoxifen and 5-fluorourasil, anticancer drugs were extremely toxic against mononuclear normal cell giving LC50 of 3.52 μg/mL and 4.05 μg/mL. The ANOVA f-test (P<0,05) showed that seed of ethanol has higher cytotoxic activity than fruit meat extract. Extract no cytotoxic activity difference between tamoxifen and 5-fluorourasil.